Electroanalysis of Candida albicans biofilms: A suitable real-time tool for antifungal testing. (1st September 2021) - Olaifa, Kayode; Nikodinovic-Runic, Jasmina; Glišić, Biljana; Boschetto, Francesco; Marin, Elia; Segreto, Francesco; Marsili, Enrico
Highlights: Electroanalysis was employed for antifungal testing against C. albicans biofilm. Chronoamperometry provided a rapid, easy-to-interpret and repeatable results. Complex Ag3 showed the highest inhibition of current output in C. albicans biofilm Abstract: Candida albicans is a fungal pathogen that accounts for more than a million death annually. Analysis of Candida biofilms and rapid assessment of antifungal therapy is a critical challenge in clinical practice. Current biochemical methods are time-consuming and expensive or require expert interpretation of the results. Hence, there is the need for a rapid anti-fungal and anti-biofilm test. While electroanalysis has been previously adopted to determine antibiotic susceptibility in bacterial biofilms, there are no studies on yeast and fungi. In this work, electroanalysis of C. albicans biofilm and evaluation of anti-biofilm activity of several antifungal compounds using screen-printed carbon electrodes (SPEs) are reported. Results are compared with standard biochemical and microscopic methods. The current output decreases by 47.5%, 73.4%, and 88.5% in biofilms treated with the antifungals fluconazole (Flz), amphotericin B (AmB), and complex Ag3, respectively, indicating the suitability of electrochemical testing for evaluation of antifungal drugs. Chronoamperometry allows measuring antifungal activity on Candida biofilm as early as 10 h after inoculation, which show promises for the development of bioelectrochemical sensors in clinical settings. Graphical abstract: Image, graphical abstract